ANALYSIS OF ENTREPRENEURSHIP CHARACTERISTICS, VENTURE CAPITAL, AND MARKETING STRATEGY ON SUCCESS OF SMALL INDUSTRY ENTERPRISES - Permatasari, Ita Rifiani (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study is to analyze the factors that influence the success of a small business because the chance of small business'potential to be improved and expanded is very wide.The population in this study is all small industrial ceramics at Dinoyo. The total sample is 30 people, selected with a non-probability method, which is the method of purposive sampling. The data analysis method used in this study is multiple regression. The results show that the characteristics of entrepreneurship and marketing strategy have a significant positive effect on the success of the business, while venture capital doesn't have a significant effect, this shows venture capital is not a variable that affects the success of the ceramic business at Dinoyo Malang.The results also show that the characteristic of entrepreneurship variables is not the biggest variable which affects the success of the business, while marketing strategy variable greatly affects the success of ceramics small industries at Dinoyo Malang. The conclusion of this study is the higher the ability of entrepreneurs in determining the marketing strategy, the higher the chances to succeed in the business. In the other hand, the characteristics of entrepreneurship variable also have substantial contribution in influencing the success of the small business.